Community Knowledge and Stigma About COVID-19: An Indonesian Perspective - Safira Grace Sondakh; I Gede Purnawinadi; Christa Vike Lotulung (Yayasan Ilomata, 2023)
Corona Virus Disease (COVID-19) is a new infectious disease caused by a type of coronavirus. The high number of positive COVID-19 cases in Indonesia has created a negative stigma against people who are exposed to it, not even positive patients who get negative stigma. Knowledge is the community's way of understanding COVID-19 and knowing how dangerous the disease is by assessing every aspect of prevention and transmission by knowing and understanding the COVID-19 disease. This study aims to determine the relationship between knowledge and stigma in society about COVID-19, so that efforts to prevent the occurrence of social stigma related to COVID-19 that are sustainable in society can be carried out. The research method uses a quantitative design with a cross-sectional approach. The sampling technique used purposive sampling with 170 respondents. The results showed that the public's knowledge about COVID-19 consisted of 88 people (51.8%) of whom the majority had sufficient knowledge. Meanwhile, community stigma about COVID-19 was found 122 people (71.8%) did not have stigma. The results of the correlation test found that the p-value was 0.441 > 0.05, meaning that there was no significant relationship between knowledge and public stigma about COVID-19. It is not enough just to know about COVID-19 to minimize stigma in the community, other factors need to be investigated.